PENGEMBANGAN LAPANGAN TGB DENGAN PARAMETER PENAMBAHAN SUMUR DAN KEEKONOMIAN DENGAN SIMULASI RESERVOIR - Putri, Devita; Abror, Hadziqul (Universitas Jember, 2025)
The Tarakan Basin in North Kalimantan is a key hydrocarbon province featuring the Meliat, Tabul, Santul, and Tarakan formations, serving as source rock, reservoir, and seal. Before 2006, the area, especially Bunyu Island, was considered a greenfield due to limited data. This changed with the successful drilling of exploration well A-01 in 2006, which confirmed oil presence in the Tabul and Meliat Formations. This study evaluates development scenarios for the TGB Field using reservoir simulation and economic analysis under a Production Sharing Contract (PSC) with a Cost Recovery scheme. CMG 2021 software was used, based on production history, petrophysical data, geological models, and pressure history. Results show that additional wells significantly improve recovery. The base case with only well A-01 yields 562,188 STB (RF 1.6%). Scenario 1 raises production to 2.99 million STB (RF 8.65%), Scenario 2 to 4.29 million STB (RF 12.38%), and Scenario 3 to 4.59 million STB (RF 13.25%). Although Scenario 3 has the best technical result, Scenario 2 is the most economically viable, with a contractor NPV of USD 1.67 million, IRR of 12%, and pay-out in 7.82 years. It also provides significant government revenue of USD 307 million.